2023
DOI: 10.1590/0037-8682-0565-2022
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Ixekizumab vs. low-dose IL-2 vs. Colchicine vs. standard of care in the treatment of patients hospitalized with moderate-to-critical COVID-19: A pilot randomized clinical trial (STRUCK: Survival Trial Using Cytokine Inhibitors)

Abstract: Background: Cases of coronavirus disease 2019 (COVID-19) requiring hospitalization continue to appear in vulnerable populations, highlighting the importance of novel treatments. The hyperinflammatory response underlies the severity of the disease, and targeting this pathway may be useful. Herein, we tested whether immunomodulation focusing on interleukin (IL)-6, IL-17, and IL-2, could improve the clinical outcomes of patients admitted with COVID-19. Methods: This multic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Similar clinical circumstances exist for dexamethasone’s effect on COVID-19 mortality, which may also be brought on by eosinophil apoptosis [ 55 ]. A recent study found that the IL-17 inhibitor ixekizumab, the indirect IL-6 inhibitor colchicine, and IL-2 to be safe but ineffective for treating COVID-19 [ 56 ]. Surprisingly, the anti-IL-17 drugs netacimab and secukinumab reduce the risk of pulmonary embolism in patients with severe COVID-19, indicating that IL-17 may be a major factor causing this complication of COVID-19, given its documented prothrombotic and procoagulant effects [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar clinical circumstances exist for dexamethasone’s effect on COVID-19 mortality, which may also be brought on by eosinophil apoptosis [ 55 ]. A recent study found that the IL-17 inhibitor ixekizumab, the indirect IL-6 inhibitor colchicine, and IL-2 to be safe but ineffective for treating COVID-19 [ 56 ]. Surprisingly, the anti-IL-17 drugs netacimab and secukinumab reduce the risk of pulmonary embolism in patients with severe COVID-19, indicating that IL-17 may be a major factor causing this complication of COVID-19, given its documented prothrombotic and procoagulant effects [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…To mitigate the potential variability introduced by chronic immune activation in COVID-19 patients, it is critical to consider that the putative administration of low-dose IL-2 in COVID-19 patients should be restricted to the convalescent phase of the disease, long after the acute inflammation has been resolved, to avoid unwanted hyperactivation of the immune response during the acute phase of the disease. To date, there have been very few pilot studies investigating the use of low-dose IL-2 in COVID-19 patients, and these have been limited to the treatment of patients with acute disease, which may explain the reported lack of clear therapeutic benefit for these patients [ 34 , 35 ]. Further work will therefore be necessary to support the potential clinical application of low-dose IL-2 in convalescent COVID-19 patients, including the retrospective analysis of the incidence of PASC in cohorts of patients treated with low-dose IL-2.…”
Section: Discussionmentioning
confidence: 99%
“…Tocilizumab proved its clinical effectiveness in patients during the coronavirus pandemic ( Io et al, 2021 ). One more approach of the treatment is using colchicine, an indirect IL-6 inhibitor, which is also applied in the treatment of coronary heart disease ( Bonifácio et al, 2023 ). Colchicine suppresses the recruitment of neutrophils, inhibits cytoskeleton metabolism, and opposes SARS-CoV-2 functionality in human cells ( Kasiri et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%